Systematic Literature Review on Blockchain-Based Knowledge Integration Models for Higher Learning Institutions - Nur Ilyana Ismarau Tajuddin; Nor Aziyatul Izni; Nurafifah Mohd Nor; Muhammad Nuruddin Sudin; Nur Aqilah Hazirah Mohd Anim; Rozi Nor Haizan; Noorashikin Md Noor; Khairi Azhar Aziz (Universiti Tun Hussein Onn Malaysia Publishing, 2025)
Indexed by MyCite